2009
DOI: 10.1007/s00441-009-0766-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human amniotic membrane grafts combined with marrow mesenchymal stem cells on healing of full-thickness skin defects in rabbits

Abstract: We have investigated the wound-healing effects of mesenchymal stem cells (MSCs) in combination with human amniotic membrane (HAM) when grafted into full-thickness skin defects of rabbits. Five defects in each of four groups were respectively treated with HAM loaded with autologous MSCs (group A), HAM loaded with allologous MSCs (group B), HAM with injected autologous MSCs (group C), and HAM with injected allologous MSCs (group D). The size of the wounds was calculated for each group at 7, 12, and 15 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…In our study, the first objective was to analyze which of all the methods described in the literature was the most effective to eliminate not only the epithelium, but also stromal cells (Yang et al 2009;Lim et al 2009;Hopkinson et al 2008;Barreto de Melo et al 2007;Kim et al 2009). We were able to establish that digestion with 1 % T/E for 30 min at 37°C completely eliminated not only the epithelium, but also the cells of the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the first objective was to analyze which of all the methods described in the literature was the most effective to eliminate not only the epithelium, but also stromal cells (Yang et al 2009;Lim et al 2009;Hopkinson et al 2008;Barreto de Melo et al 2007;Kim et al 2009). We were able to establish that digestion with 1 % T/E for 30 min at 37°C completely eliminated not only the epithelium, but also the cells of the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the combination of amniotic membrane treatment and MSCs has shown better therapeutic effects than amniotic membrane treatment alone in patients with ocular chemical burns, skin defects, and articular cartilage defects. 47,48 Thus for some severe ocular disorders, the combination of amniotic membrane treatment and MSCs or MSC-CMT might be a promising therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) or epidermal cells have been demonstrated playing an eff ective role in promoting wound healing when injected into the skin defect, either alone or in combination with human amniotic membrane (HAM) (Kim et al 2008). Sung has shown that HAM loaded with MSCs improves wound healing (Kim 2009). Umbilical cord blood contains hematopoietic as well as non-hematopoietic MSCs, the latter also known as CBEs (Cord Blood Embryonic-like stem cells) (Branski et al 2009).…”
Section: Introductionmentioning
confidence: 99%